Some New Fixed Point Theorems in Partial Metric Spaces with Applications. (29th March 2017) - Pant, Rajendra; Shukla, Rahul; Nashine, H. K.; Panicker, R.
Abstract : Recently, a number of fixed point theorems for contraction type mappings in partial metric spaces have been obtained by various authors. Most of these theorems can be obtained from the corresponding results in metric spaces. The purpose of this paper is to present certain fixed point results for single and multivalued mappings in partial metric spaces which cannot be obtained from the corresponding results in metric spaces. Besides discussing some useful examples, an application to Volterra type system of integral equations is also discussed.